1997
DOI: 10.1292/jvms.59.1017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Zinc Content on 65Zn Metabolism in Mice.

Abstract: ABSTRACT. 65 Zn is one of the induced radioactive nuclides which are generated in power reactors. In the present experiment, several parameters of 65 Zn metabolism were studied in mice maintained on diets with various zinc contents from 45 to 4,500 mg/kg to evaluate the efficacy of the dilution method for radiation protection against internal contamination with 65 Zn. Gastrointestinal absorption of 65 Zn was suppressed and its excretion accelerated as the dietary zinc content increased over a wide range. Clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Sato et al [21] reported a minimum absorption efficiency of approximately 0.8%, and for example, if the AE min is set at 0.007 mg/mg, then the model predicts such a trend (Fig. Sato et al [21] reported a minimum absorption efficiency of approximately 0.8%, and for example, if the AE min is set at 0.007 mg/mg, then the model predicts such a trend (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Sato et al [21] reported a minimum absorption efficiency of approximately 0.8%, and for example, if the AE min is set at 0.007 mg/mg, then the model predicts such a trend (Fig. Sato et al [21] reported a minimum absorption efficiency of approximately 0.8%, and for example, if the AE min is set at 0.007 mg/mg, then the model predicts such a trend (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Sato et al [21] reported a minimum absorption efficiency of approximately 0.8%, and for example, if the AE min is set at 0.007 mg/mg, then the model predicts such a trend (Fig. However, it is likely that zinc concentrations in mice are regulated homeostatically up to a dietary zinc concentration of approximately 1,350 mg/kg [21]. However, no data was found in the literature for model calibration at high dietary zinc concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…The transgenic mice were given drinking water containing varying amounts of ZnSO 4 (500, 1000 and 5,000 ppm Zn) or CuSO 4 (100 and 300 ppm Cu) for periods of up to 8 weeks, and their bodyweights were monitored and general health was observed on a daily basis. Maximum metal levels chosen for the pilot experiment were based on published experiments in which mice or rats had been fed with Cu or Zn salts (Cunnane et al 1986;Massie and Aiello 1979;Olafson 1983;Pocino et al 1991Pocino et al , 1990Sato et al 1997;Zhang et al 1994). After 2 weeks, mice fed with 5,000 ppm Zn showed a considerably reduced water intake, and appeared sickly and dehydrated, at which point this feeding dose was ceased.…”
Section: Feeding Mice With Metalsmentioning
confidence: 99%
“…In a previous study, zinc concentrations in tissues were maintained homeostatically up to a dietary zinc level of 1,350 mg/kg. Uptake of zinc from this diet was estimated to be 1.5 mg/kg/day [14]. Assuming that the safe level is 1/10 of the upper limit, daily zinc burden should not exceed 0.15 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is mainly excreted into feces via the pancreatic juice and intestinal mucosal cells [8]. Endogenous fecal excretion of zinc increases as dietary zinc intake increases [18], and zinc concentrations in various tissues are maintained homeostatically over a wide range of dietary zinc levels [1,14]. These observations suggest that animals have a high potential for excreting excess zinc from the body.…”
Section: Discussionmentioning
confidence: 99%